Penerapan Reaktor Biogas Skala Rumah Tangga dari Kotoran Domba sebagai Solusi Energi di Umroh Farm - Idris, Muhammad; Umroh, Bobby; Jufrizal, Jufrizal; Hermawan, Indra; Harahap, Uun Novalia (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2025)
This Community Service activity addresses sheep manure waste issues at Umroh Farm, Patumbak Village, Deli Serdang. Waste buildup causes odor and environmental pollution despite its potential as biogas material. The solution was implementing appropriate technology by constructing a household-scale biogas reactor. Activities included participatory training, equipment assembly, and field trials. The digester, with a ±200-liter capacity, was made from plastic drums and equipped with input-output, cleaning, and gas collection lines. The implementation produced an average of 0.015 m³ of biogas per hour, with fire ignition lasting 1–2 seconds. The program reduced livestock waste, improved farmers’ awareness and skills and supported clean energy and climate change mitigation goals. Its success shows that simple biogas technology can provide an integrated solution for environmental management and community empowerment.